Development of an EvaGreen based real-time RT-PCR assay for rapid detection, quantitation and diagnosis of goose calicivirus. (February 2020) - Lin, Su; Zhang, Shizhong; Wang, Shao; Xie, Kaichun; Jiang, Dandan; Xiao, Shifeng; Chen, Xiuqin; Chen, Shaoying
Abstract: An unclassified calicivirus (CV) detected in geese was recently reported and proposed as a new member of the family Caliciviridae . There is limited information about the epidemiology, etiology and detection method of goose-origin CV (GCV) to date. In this study, an EvaGreen based fluorescence quantitative real-time RT-PCR assay was developed and optimized for the detection of GCVs. The assay sensitively detected GCV RNA template with a good linear standard curve. We also demonstrated the specificity and reproducibility of the detection method for GCVs. Thus, the method developed in this study will benefit the investigation of possible sporadic outbreaks of CV infections in geese, as well as epidemiological and etiological studies of GCVs. Highlights: An EvaGreen based real-time RT-PCR assay was developed for detection and quantitation of newly emerging goose caliciviruses. The assay provides quantitative data that may be used to inform epidemiological and etiological studies.